A Multidisciplinary Comparative Analysis of the Story of Prophet Noah in the Qur’an and the Bible - Ning Ratna Sinta Dewi; Siti Wahdaniah Nur Annisa; Rabiatul Adawiyah; Grandis Rangga Putra; Muhammad Rauf Amrullah; Andryan Kurnia Pratama; Muhammad Rizki Saputra; Faiz Laksmana Saragih (Muqaranah Al-Adyan: Multidisciplinary Perspective on Religions, 2026)
This study examines the story of Prophet Noah in the Qur’an and the Bible through a multidisciplinary comparative approach encompassing theological, historical, literary, and socio-religious perspectives. The aim of this research is to identify the similarities and differences in narrative structure, theological emphasis, and moral messages conveyed by both sacred texts, as well as to understand their implications for religious understanding among believers. The method employed is a qualitative library research approach with a comparative narrative analysis, utilizing primary sources from the Qur’an and the Bible alongside relevant secondary literature. The findings reveal that the Qur’an presents the story of Prophet Noah thematically, emphasizing the dimensions of prophetic preaching (da‘wah), steadfast faith, and the rejection of truth by his people. In contrast, the Bible offers a more chronological narrative, focusing on God’s covenant, the salvation of Noah’s family, and the manifestation of divine law. From a literary perspective, the Qur’an employs a concise and symbolic rhetorical style, whereas the Bible provides a more descriptive and historical account. Theologically, both texts affirm the oneness and justice of God, yet differ in their emphasis on the mechanisms of salvation and the nature of the relationship between God and humanity. In conclusion, despite differences in narrative approach and theological focus, both traditions convey shared universal values such as faith, obedience, patience, and moral lessons derived from past communities. This multidisciplinary approach enriches interreligious understanding and opens pathways for more inclusive dialogue within comparative religious studies